1 0 0 + 9 9 1 + 9 9 + 9 8 1 + 9 8 + 9 7 1 + ⋯ + 3 + 2 1 + 2 + 1 1
If the above expression equals k , find k 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Same logic as Brandon Monsen 's, just different presentation.
k = n = 1 ∑ 9 9 n + n + 1 1 = n = 1 ∑ 9 9 ( n + 1 + n ) ( n + 1 − n ) n + 1 − n = n = 1 ∑ 9 9 n + 1 − n n + 1 − n = n = 1 ∑ 9 9 ( n + 1 − n ) = n = 2 ∑ 1 0 0 n − n = 1 ∑ 9 9 n = 1 0 0 − 1 = 9
⇒ k 2 = 9 2 = 8 1
Can you please how you moved from fourth line to fifth line ??
Log in to reply
Expanding the two summation series.
\begin{aligned} \sum_{n=2}^{100}\sqrt{n} - \sum_{n=1}^{99}\sqrt {n} & =(\sqrt{2} +\sqrt {3}+\sqrt {4} +... +\sqrt{100})-(\sqrt {1}+\sqrt {2}+\sqrt {3}+...+\sqrt {99})\\ & = \sqrt {100}-\sqrt {1} \end{aligned} \end {equation}
Problem Loading...
Note Loading...
Set Loading...
First, let's start rationalizing the denominators. To do this, we can multiply the term 1 0 0 + 9 9 1 by 1 0 0 − 9 9 1 0 0 − 9 9 to get 1 0 0 − 9 9 .
We can repeat this same process all the way down our sum, and end up with 1 0 0 − 9 9 + 9 9 − 9 8 + 9 8 − 9 7 + . . . + 3 − 2 + 2 − 1
Conveniently, all of the terms except for 1 0 0 − 1 cancel! This is called a Telescoping Sum .
Now, we can conclude that our sum is k = 1 0 0 − 1 = 1 0 − 1 = 9 , so k 2 = 8 1